Penghambatan Enzim Asetilkolinesterase Pada Penyakit Alzheimer Dari Ekstrak Etanol Daun Kelor (Moringa oleifera Lam.) - Yonathan Tri Atmodjo Reubun (Jurnal Farmasi Indonesia, 2021)
Moringa leaves have been recognized by the public as a treatment. One such disease is Alzheimer's disease where the way this plant works is to inhibit the damage that occurs in the nervous system in the brain. The purpose of this study was to obtain ethanol extract of Moringa leaves by carrying out a phytochemical screening process to determine the chemical content contained in these plants. The moringa leaves obtained were subjected to a grinding process to obtain simplicia powder. After that, the extraction is done by soaking the Moringa leaves with 96% ethanol for 11 times until the extract is perfect. After that, the concentration is done with a Rotary Evaporator until you get a thick extract of Moringa leaves. After that, the thick extract is followed by the Freeze Drying process to get a thick extract that is stable and can hold in storage. After that, the extract was tested against the inhibition of the acetylcholinesterase enzyme based on the Ellman method, the IC50 yield of Moringa leaf extract was 819.7517 ppm. Meanwhile, Eserin positive control with an IC50 value of 5.010 ppm. Acetylcholinesterase inhibition kinetics were competitive. So it is said that Moringa oleifera extract has an effect on the treatment of Alzheimer's disease.